The AGOA as stepping stone for USA–Africa free trade agreements - (:unkn) unknown (My University, 2018)
Purpose The purpose of this paper is to show how the pattern of trade relations between the USA and African countries is gradually shifting toward reciprocity. It therefore demonstrates that the African Growth and Opportunity Act (AGOA) was conceived to be a building block toward future bilateral trade agreements. Design/methodology/approach This paper adopts a historical approach to the USA’s policy toward Africa in general and in trade matters in particular. It critically reviews the chronology of US involvement in the continent. Findings Although it was designed as a preferential trade arrangement, AGOA was intended to evolve into reciprocal trade agreements. This is what the USA started doing even prior to the entry into force of the AGOA, by entering into Trade and Investment Framework Agreements with individual countries or blocs. It also transpires that the deployment comes as a response to the European Union which is already engaged in the redefinition of its own trade relations with Africa since 2004. Originality/value The paper is important in many respects. Not only it is a study of the US practice as preference-granting country, but it is also interested in the typology of trade agreements concluded by the USA in other regions of the world. This is important to indicate and analyze the types of provisions African countries should be expected to face when the time of entering into reciprocal binding trade treaties arrives.
Keywords: African Research